Masseter nerve-based facial palsy reconstruction - Park, Hojin (Arch Craniofac Surg, 2020)
Facial paralysis is a devastating disease, the treatment of which is challenging. The use of the masseteric nerve in facial reanimation has become increasingly popular and has been applied to an expanded range of clinical scenarios. However, appropriate selection of the motor nerve and reanimation method is vital for successful facial reanimation. In this literature review on facial reanimation and the masseter nerve, we summarize and compare various reanimation methods using the masseter nerve. The masseter nerve can be used for direct coaptation with the paralyzed facial nerve for temporary motor input during cross-facial nerve graft regeneration and for double innervation with the contralateral facial nerve. The masseter nerve is favorable because of its proximity to the facial nerve, limited donor site morbidity, and rapid functional recovery. Masseter nerve transfer usually leads to improved symmetry and oral commissure excursion due to robust motor input. However, the lack of a spontaneous, effortless smile is a significant concern with the use of the masseter nerve. A thorough understanding of the advantages and disadvantages of the use of the masseter nerve, along with careful patient selection, can expand its use in clinical scenarios and improve the outcomes of facial reanimation surgery.